2013
DOI: 10.1038/nn.3315
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-specific network connectivity increases underlie accurate spatiotemporal memory retrieval

Abstract: The medial temporal lobes, prefrontal cortex, and parts of parietal cortex form the neural underpinnings of episodic memory, which includes remembering both where and when an event occurred. Yet how these three key regions interact during retrieval of spatial and temporal context remains largely untested. Here, we employed simultaneous electrocorticographical recordings across multiple lobular regions, employing phase synchronization as a measure of network functional connectivity, while patients retrieved spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
277
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 294 publications
(320 citation statements)
references
References 54 publications
42
277
1
Order By: Relevance
“…Remarkably, the place cells responsive to the area where the item was delivered became active during recall of the item, closely mirroring the reactivation of place cells during replay events in rodents. Although free recall in humans is not likely to correspond to sharp-wave ripple events (Watrous et al 2013), the time course of reactivation was similar to a typical sharp-wave ripple event in rodents, and may therefore reflect a qualitatively similar phenomenon. The place cell activity during recall of events or items likely brings to mind the spatial context in which the events and items were experienced, creating a fully reconstructed memory for what was experienced, along with where it was experienced.…”
Section: Memory Consolidation and Retrievalmentioning
confidence: 85%
“…Remarkably, the place cells responsive to the area where the item was delivered became active during recall of the item, closely mirroring the reactivation of place cells during replay events in rodents. Although free recall in humans is not likely to correspond to sharp-wave ripple events (Watrous et al 2013), the time course of reactivation was similar to a typical sharp-wave ripple event in rodents, and may therefore reflect a qualitatively similar phenomenon. The place cell activity during recall of events or items likely brings to mind the spatial context in which the events and items were experienced, creating a fully reconstructed memory for what was experienced, along with where it was experienced.…”
Section: Memory Consolidation and Retrievalmentioning
confidence: 85%
“…In addition to the relationship between increased coherence within specific frequency bands and better memory performance reported in some studies (Benchenane et al 2010;Fell et al, 2008;Watrous et al 2013), animal studies also have shown that direct electrical stimulation can entrain action potentials (i.e., spikes) and oscillatory activity (Anastassiou, Perin, Markram, & Koch, 2011;Fröhlich & McCormick, 2010). Thus, while the exact mechanisms whereby coordinated low-frequency oscillations between indirectly connected brain areas facilitate network function and behavior more broadly remain to be fully elucidated, macrostimulation that modulates synaptic and/or spiking activity in the targeted neuronal populations may be a promising approach to modulating oscillatory dynamics and function of a network.…”
Section: Synthesis: Network Based Effects Of Neurostimulation On Memomentioning
confidence: 96%
“…Indeed, past neuroimaging studies have argued that lateral frontal and parietal regions are part of the core networks associated with memory encoding (Blumenfeld & Ranganath, 2007;Nyberg et al, 1996;Tulving et al, 1994) and/or retrieval (Cabeza et al, 2004;Cabeza et al, 2003Cabeza et al, , 2002Donaldson et al, 2001;Nyberg et al, 1996;Tulving et al, 1994;Vilberg & Rugg, 2008). More recent theoretical and empirical studies have argued that these regions are part of a larger network of interacting brain regions subserving memory (King, de Chastelaine, Elward, Wang, & Rugg, 2015;Schedlbauer, Copara, Watrous, & Ekstrom, 2014;Watrous et al, 2013). Thus, a key prediction is that disruption of extra-hippocampal nodes should also produce impairments in memory function.…”
Section: Hypothalamic Stimulationmentioning
confidence: 99%
See 2 more Smart Citations